1996
DOI: 10.1007/bf02337884
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake and utilisation by nursing bearded seal (Erignathus barbatus) pups from Svalbard, Norway

Abstract: In this study we measure energy intake via milk in nursing bearded seal (Erignathus barbatus) pups and determine how this energy is allocated into metabolism and storage of new tissues. This was accomplished using longitudinal mass gain records and the doubly labelled water technique on nursing pups in combination with cross-sectional data on changes in milk composition from bearded seal mothers. The pups (n = 3) were all less than a week old at the start of the experiments. Pups gained 3.3 +/- 0.4 kg.day-1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Field metabolic rates (FMR) for 23‐month Australian sea lions were 3·95 times basal metabolic rates (BMR) predicted for adult terrestrial animals of equivalent size (Kleiber 1975). Although this is the first study to measure FMR in a juvenile sea lion, results fall within the range of rates reported for young pinnipeds (phocids: 2·7–6·0 times BMR (Reilly 1991; Kretzmann, Costa & LeBoeuf 1993; Lydersen & Hammill 1993; Lydersen & Kovacs 1996; Lydersen et al. 1996), otariids: 3·25–3·84 times BMR (Arnould et al.…”
Section: Discussionsupporting
confidence: 81%
“…Field metabolic rates (FMR) for 23‐month Australian sea lions were 3·95 times basal metabolic rates (BMR) predicted for adult terrestrial animals of equivalent size (Kleiber 1975). Although this is the first study to measure FMR in a juvenile sea lion, results fall within the range of rates reported for young pinnipeds (phocids: 2·7–6·0 times BMR (Reilly 1991; Kretzmann, Costa & LeBoeuf 1993; Lydersen & Hammill 1993; Lydersen & Kovacs 1996; Lydersen et al. 1996), otariids: 3·25–3·84 times BMR (Arnould et al.…”
Section: Discussionsupporting
confidence: 81%
“…Burns (1981) claimed that weaning in bearded seals is abrupt, with the pups simply being deserted by their mothers. In contrast, Lydersen et al (1996) suggested that bearded seal pups may suckle longer than some other phocid pups and that weaning is less abrupt than among other phocid species. A mixture of milk and prey has been recorded in bearded seal pup stomachs (RoÈ mer and Schaudinn 1900), which indicates that pups commence foraging while still being nursed.…”
Section: Introductionmentioning
confidence: 95%
“…However, during the past decade concerted efforts have greatly increased our knowledge of bearded seal natural history, and their importance to arctic ecosystems (e.g. Hammill et al, 1994; Lydersen Kovacs et al, 1996;Lydersen et al, 1996;Andersen et al, 1999;Lydersen and Kovacs, 1999;Gjertz et al, 2000;Krafft et al, 2000;Lydersen et al, 2001;Marshall et al, 2001;Van Parijs et al, 2001;Lydersen et al, 2002;Van Parijs et al, 2003;Van Parijs et al, 2004;Davies et al, 2006;Marshall et al, 2006;Van Parijs and Clark, 2006;Dehn et al, 2007;Risch et al, 2007). Analyses of stomach contents and recent stable isotope analyses demonstrate that bearded seals are generalist foragers (e.g.…”
Section: Introductionmentioning
confidence: 99%